2014
DOI: 10.3389/fpsyg.2014.00631
|View full text |Cite
|
Sign up to set email alerts
|

Fluency and belief bias in deductive reasoning: new indices for old effects

Abstract: Models based on signal detection theory (SDT) have occupied a prominent role in domains such as perception, categorization, and memory. Recent work by Dube et al. (2010) suggests that the framework may also offer important insights in the domain of deductive reasoning. Belief bias in reasoning has traditionally been examined using indices based on raw endorsement rates—indices that critics have claimed are highly problematic. We discuss a new set of SDT indices fit for the investigation belief bias and apply t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“… 2 The confidence ratings were collected with the aim to conduct signal detection theory (SDT) analyses (cf., Dube, Rotello, & Heit, 2010 ; Trippas, Handley, & Verde, 2014 ), which we did not report given that they converged with the reported analyses. As a consequence, our confidence rating scale has a very low resolution, potentially negatively impacting the possibility of uncovering meaningful patterns.…”
contrasting
confidence: 46%
“… 2 The confidence ratings were collected with the aim to conduct signal detection theory (SDT) analyses (cf., Dube, Rotello, & Heit, 2010 ; Trippas, Handley, & Verde, 2014 ), which we did not report given that they converged with the reported analyses. As a consequence, our confidence rating scale has a very low resolution, potentially negatively impacting the possibility of uncovering meaningful patterns.…”
contrasting
confidence: 46%
“…Moreover, individuals usually only reason when the conclusion is unbelievable (i.e., they do not engage in reflection when the conclusion is believable). The conditional willingness to reason is called motivated reasoning (Kunda 1990 ) and results in increased accuracy when assessing the validity of unbelievable conclusions (Evans et al 1983 ; Trippas et al 2014 ). The interaction between believability and validity delivers an example for the intuition-deliberation trade-off.…”
Section: Cognitive Psychology Of Reasoningmentioning
confidence: 99%
“…Moreover, it is generally indicated that there are correct solutions, as can be seen in the following instructions from a study by Morley et al (2004) : “This experiment is designed to find out how people solve logical problems … Please take your time and be sure that you have the logically correct answer before deciding” (p. 8, italics added for emphasis). Even the most recent reasoning papers continue to use phrases such as, “If you judge that the conclusion necessarily follows from the premises, you should answer ‘Valid,’ otherwise you should answer ‘Invalid’ …” ( Trippas et al, 2014 , p. 11). We suggest that without instructing participants that there is a correct or valid answer to a given problem it is unlikely that standard effects from the reasoning literature would arise.…”
Section: The Importance Of Focusing On Individual Differencesmentioning
confidence: 99%